Competition between Mullins and curvature effects in the wrinkling of stretched soft shells. (1st April 2022) - Wang, Ting; Yang, Yifan; Fu, Chenbo; Xu, Fan
Abstract: A highly stretched hyperelastic shell exhibits a coupling behavior of local wrinkling and global bending within the stability boundary, and curvature resists and can even suppress surface wrinkles beyond a critical threshold. Here, we report a novel phenomenon that smooth surface maintains upon stretching a soft shell, while wrinkles emerge upon unloading, which implies a nonlinear interplay between curvature and Mullins (stress softening and residual strain) effects in the entire loading–unloading cycle. To quantitatively account for such material damage (Mullins effect) and explore the underlying mechanism, we develop a finite-strain pseudo-elastic shell model that can predict the entire post-buckling morphology evolution. Results reveal three representative scenarios of morphology evolution of stretched soft shells. For shells within a certain range of aspect ratios and curvatures, no wrinkle appears upon loading while wrinkling occurs during the unloading process. For shells with smaller curvature, wrinkles exist during loading and unloading, while the shells with larger curvature remain constantly smooth in the loading–unloading process. The Mullins effect advances wrinkle formation, while curvature resists instability occurrence. Understanding such coupling effects between material and curvature on morphological evolution is critical for wrinkle-tunable design of functional surfaces. Highlights: We have uncovered a nonlinear competition between Mullins and curvature effects in the wrinkling of stretched soft shells. The Mullins effect advances wrinkle formation, while curvature resists wrinkling occurrence. We have developed a finite-strain pseudo-elastic shell model that can describe Mullins effect. Results reveal three representative scenarios of morphology evolution of stretched soft shells. Understanding the coupling effects between material and curvature on morphology evolution is crucial for wrinkle-tunable design.